Konseling Pranikah: Sebuah Upaya Meredukasi Budaya Pernikahan Dini di Kecamatan Pulung Kabupaten Ponorogo - Diana Ariswanti Triningtyas; Siti Muhayati (JKI (Jurnal Konseling Indonesia), 2017)
The long-term goal of this study is to determine the factors that underlie the early marriage and provide understanding to the people of Pulung Ponorogo against the psychological impact of early marriage. To achieve these objectives, the researcher conducted a research entitled: "Premarital Counseling: An Effort to Reduce Early Marriage Culture in Pulung Ponorogo". This research was conducted in Pulung Ponorogo. In this study, researchers used descriptive qualitative research design. The data was collected by using participant observation and indepth interview to each informant by asking questions in the form of interview and documentation guidance. The analysis is done through the following stages of information gathering phase, data segregation phase, data presentation stage and conclusion drawing stage. Meanwhile, to ensure the validity of the data, the researchers used the technique of triangulation of sources that is by checking the information submitted by the informant. The results showed that in general, early marriage has problems and affects the psychological impact of individuals. One effort is made to reduce through premarital counseling. This service is provided so that the individual understands the role of husband and wife candidate to organize the life in fostering the household.